Fitness professionals: narrative review. - Ramos, Liliana (2020)
The increasing number of fitness professionals is one of the results associated with the growth of this industry. Understanding the sociodemographic characteristics and different variables related to the intervention of fitness professionals in Portugal will increase the knowledge about this work activity and can also contribute to the improvement of their working and living conditions. This study aims to carry out a narrative review in order to identify the main characteristics of fitness professionals. This identification will allow the building of the conceptual bases necessary for the construction of an instrument that will help to characterize these professionals. The research obtained seven results, three of them reports and four descriptive studies. Most of the characterization variables of fitness professionals refer to age, gender, place of residence and qualifications regarding sociodemographic aspects. Regarding aspects related to the profession, the professionals were characterized mainly in terms of hours of work, salary and the functions performed. Based on the results, the main characteristics were identified and allow us to propose a new evaluation instrument: a questionnaire that will characterize fitness professionals in Portugal - “VIDAPROFIT”.